Human Development, Banking Development and the Quality of Local Government: The Case of Indonesia - Dewanti Cahyaningsih; Irwan Trinugroho (Universitas Hayam Wuruk Perbanas, 2017)
We extend the study of Trinugroho et al. (2015) by focusing on the effect of human development on banking development and the moderating effect of the quality of local government on the link between human development and banking development. We use unique data set by disentangling the type of banks (commercial bank, rural bank, and the total of both) to measure financial development. This research uses panel data at the provincial level for the period of 2010-2014. Generally, it could be concluded that human development has positive effect on banking development. To some extent, the quality of local government is found to strengthen the impact of human development on banking development. Â